KEADILAN ORGANISASIONAL TERHADAP ALTRUISME WIDYAISWARA SENI DAN BUDAYA - Farika Chandrasari (Jurnal Pendidikan Seni dan Industri Kreatif, 2020)
The current research was carried out based on organizational justice studies aiming at portraying the process of organizational justice occurring in an organization. Organizational justice is a tool to measure the employees’ sense of justice in the organization in which they work. Organizational justice in this research comprises distributive justice and procedural justice. The creation of ideal organizational justice will naturally bring about better behavioural condition of the employees manifested in increasing the willingness to do things that bring advantages to others, known as altruism. Altruism is one of the basic dimensions of Organization Citizenship Behavior (OCB), which represents the behavior of a person who always promotes the vision and mission of his organization. The subjects of the research were 45 arts and culture master trainers. Questionnaires with Likert 4 interval scale were distributed directly to the research subjects. Data were analyzed using the SPSS program with simple linear regression analysis. The results of data analysis demonstrate that distributive justice and procedural justice are significant towards altruism.